FORMULASI PADAT RHIZOBAKTERIA INDIGENUS BACILLUS THURINGIENSIS TS2 DAN WAKTU PENYIMPANAN UNTUK MENGENDALIKAN PENYAKIT PUSTUL BAKTERI XANTHOMONAS AXONOPODIS PV. GLYCINES - Yanti, Yulmira; Habazar, Trimurti; Resti, Zurai (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
Solid formulations of indigenous rhizobacteria Bacillus thuringiensis TS2 and storage time to control bacterial pustule disease Xanthomonas axonopodis pv. glycines. Bacterial pustule disease caused by Xanthomonas axonopodis pv. Glycines is a major constraint in soybean cultivation. Indigenous rhizobacteria Bacillus thuringiensis TS2 from soybean rhizosphere acquired from previous research is the best isolate which can control soybean bacterial pustule disease and increase growth rate of soybean. To increased its stability and interaction with soybean plants, Bacillus thuringiensis TS2 was urged to test furthermore especially its formulation with based formula tapioca powder, peat and bulk. The most effective storage time also need to test. Result showed that all rhizobacterial formula had ability to decrease incidence of bacterial pustule disease compared to control. Moreover, all the three formula could increase plant growth, total of leaves, total of branch and yields. Flowering time was also advanced by 1-8 days compared to control. Decreasing of disease rate and increasing of plant growth rate variated between different formulations.